2015
DOI: 10.18632/oncotarget.3016
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DNA methyltransferase as a novel therapeutic strategy to overcome acquired resistance to dual PI3K/mTOR inhibitors

Abstract: Dual PI3K/mTOR(phosphatidylinositol 3-kinase/mammalian target of rapamycin) inhibitors are being evaluated clinically for the treatment of tumors with a hyperactivated PI3K/mTOR pathway. However, unexpected outcomes were obtained in clinical studies of cancer patients with an aberrant PI3K pathway. In clinical trials, applicable combination regimens are not yet available. In this study, using an integrated analysis of acquired BEZ235-resistant nasopharyngeal carcinoma cells, we demonstrate that DNA methyltrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…These are both involved in the negative regulation of mTOR (Qian et al. ). Ppp2r2b activation is known to be involved in the negative control of cell growth and division.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These are both involved in the negative regulation of mTOR (Qian et al. ). Ppp2r2b activation is known to be involved in the negative control of cell growth and division.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we also observed increased expression of the Ppp2r2b and Prkag3 genes. These are both involved in the negative regulation of mTOR (Qian et al 2015). Ppp2r2b activation is known to be involved in the negative control of cell growth and division.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical studies have found that nasopharyngeal cell lines resistant to the PI3K/mTOR inhibitor BEZ235 are characterized by low expression of PTEN and the PP2A subunit PPP2R2B as a result of promoter hypermethylation [48]. BEZ235 refractory cell lines were modestly re-sensitized with the addition of decitabine [48].…”
Section: Clinically Targeting the Pi3k Pathway In Pi3k-activated Solimentioning
confidence: 99%
“…BEZ235 refractory cell lines were modestly re-sensitized with the addition of decitabine [48]. Further research suggests the importance of DNMT3b function in promoting mTORC2 activation in melanoma; genetic loss of DNMT3 expression results in promoter hypomethylation and increased expression of mir-196b, which targets the mTORC2 component RICTOR.…”
Section: Clinically Targeting the Pi3k Pathway In Pi3k-activated Solimentioning
confidence: 99%